Effectiveness of Manual Therapy for Pain in Neck Pain Patients: A Systematic Review and Meta-Analysis - Apriliyani, Yuyun; Wahyuni, Wahyuni (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Neck pain (NP) is a musculoskeletal public health problem that is often experienced, especially by modern society, with a high prevalence that can cause disability. Neck pain can be treated with various physiotherapy modalities, one of which is manual therapy/manipulation of the cervical spine. This study aims to determine the effectiveness of manual therapy in reducing pain in neck pain patients. Subjects and Method: This research is a systematic review and meta-analysis study, using PICO as follows, P= neck pain patients, I= manual therapy, C= other than manual therapy, O= reduction in pain. The articles included in this research were articles taken from several databases including Google Scholar, PubMed, NCBI, Science Direct, Embase, and Springer Link between 2010 and 2023. The keywords used to search for articles were: